(untitled) (American & British Studies Annual, 2011)
This article briefly outlines a history of Bildungsroman and provides an overview of theories of the genre and a critical assessment of them. It argues that the genre, notwithstanding some critical opinions to the contrary, is still a very potent literary form despite the fact that it came into existence in a particular historical and literary situation of eighteenth-century Germany. The genre’s flexibility allowed for variations and modifications that ensured its contemporary viability in Anglo-American literatures. While the concern with the individual’s emergence from an immature state of childhood to adult maturity, and with individual’s socialization remaining the core focus of the Bildungsroman, studies of the form have lately become involved in the discussions of ethnic and racial identification, of biculturality, of the situation of an individual in a liminal position. This makes Bildungsroman a genre especially important in contemporary American literature.